Oral high-dose sertraline-induced acute pancreatitis: a case report and literature review - Wu, Xiaoying; Duan, Liwei; Ma, Linhao (Frontiers in Medicine, 2025)
Acute pancreatitis (AP) is characterized by acute inflammation and pancreatic injury, with gallstones and chronic alcohol use representing the most common etiologies. Although drug-induced pancreatitis (DIP) accounts for fewer than 3% of AP cases, its recognition as a significant contributor to AP is growing. Sertraline, a widely prescribed selective serotonin reuptake inhibitor (SSRI), is associated with diverse adverse effects, even at therapeutic doses. We present a case of a 27-year-old female with a history of depression who developed mild acute pancreatitis following a sertraline overdose. Diagnostic evaluation, including computed tomography (CT) and serological analysis, revealed pancreatic parenchymal swelling and elevated serum amylase levels, confirming AP. Other potential causes were systematically excluded. The patient’s condition resolved following drug discontinuation and standard supportive therapy. This case underscores the need for heightened clinical awareness of SSRI-associated pancreatitis, particularly in the context of overdose.